2016
DOI: 10.1177/0192623316672352
|View full text |Cite
|
Sign up to set email alerts
|

Is It Adverse, Nonadverse, Adaptive, or Artifact?

Abstract: One of the principal challenges facing a toxicologic pathologist is to determine and differentiate a true adverse effect from a non-adverse or an adaptive response. Recent publications from the Society of Toxicologic Pathology (STP) and the European STP provide guidance for determining and communicating adversity in nonclinical toxicology studies. In order to provide a forum to inform and engage in a discussion on this important topic, a continuing education (CE) course was held during the 2016 STP Annual meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…However, these findings lacks relevance for humans because of differences in anatomical structures 32 . Even though squamous metaplasia is an adaptive or protective change, it should be considered an adverse effect because of the severity of the lesion and concomitant degenerative/necrotic and/or hyperplastic changes 33 . Interestingly, the grade of squamous metaplasia of lung in our study is found to be more severe than that in 13-week inhalation study of PHMG•HCl(Inhalation concentration: 0 mg/m 3 , 0.13 mg/m 3 , 0.4 mg/m 3 , and 1.20 mg/m 3 ) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings lacks relevance for humans because of differences in anatomical structures 32 . Even though squamous metaplasia is an adaptive or protective change, it should be considered an adverse effect because of the severity of the lesion and concomitant degenerative/necrotic and/or hyperplastic changes 33 . Interestingly, the grade of squamous metaplasia of lung in our study is found to be more severe than that in 13-week inhalation study of PHMG•HCl(Inhalation concentration: 0 mg/m 3 , 0.13 mg/m 3 , 0.4 mg/m 3 , and 1.20 mg/m 3 ) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial toxicities, such as cardiomyopathy, hepatic steatosis, pancreatitis, skeletal myopathy, lactic acidosis and neuropathy (33), have been associated with certain nucleoside analogs. In vivo , the extent of systemic re-distribution of 2′-F-purines appears to be minimal following generation from GalNAc–siRNAs in liver and kidney and, to date, there is no evidence of liver failure or nephropathy in clinical (33) or pre-clinical (34) studies with STC or ESC GalNAc–siRNAs. At completion of the 2-year rat carcinogenicity study where rats were dosed weekly with up to 100 mg/kg of two STC GalNAc–siRNA conjugates containing 22 2′-F-ribonucleotides, treatment-related ultrastructural changes involving mitochondria observed in liver hepatocytes and skeletal myocytes (soleus muscle) were limited to elongated and ring-shaped/cup-shaped mitochondrial profiles and enlarged mitochondria in animals given either ≥10 mg/kg of revusiran or 30 mg/kg of siTTR-3.…”
Section: Discussionmentioning
confidence: 99%
“…Of these two ultrastructural findings, enlargement of mitochondria was the only finding not seen in some control animals, whereas elongated mitochondria were occasionally observed in the hepatocytes of control animals, which suggested the incidence of these findings was not solely related to chronic administration of revusiran or siTTR-3. Thus, utilizing ‘a weight of evidence approach’, the ultrastructural mitochondrial changes that were observed in affected hepatocytes and myocytes (i.e., the elongation and enlargement) were not associated with plasma lactate elevations, or with adverse changes such as mitophagy, mitochondrial degeneration/necrosis or alterations in cristae morphology (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, in several cases and based on experts’ judgment, a dose might be considered as creating adversity due to the disturbance of a set of endpoints which in isolation cannot be considered as adverse or due to their nature or due to the size of disturbance [32,33]. Further effort is needed to reach consensus among regulatory toxicologists regarding in which level each effect should be consider adverse [[34], [35], [36], [37]]. This long-avoided discussion is now necessary also in order to set the critical effect sizes for the benchmark dose [38].…”
Section: Discussionmentioning
confidence: 99%